2015
DOI: 10.1038/srep14753
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of trans-proteolytic activity of Chikungunya virus capsid protease and development of a FRET-based HTS assay

Abstract: Chikungunya virus (CHIKV) capsid protein (CVCP) is a serine protease that possesses cis-proteolytic activity essential for the structural polyprotein processing and plays a key role in the virus life cycle. CHIKV being an emerging arthropod-borne pathogenic virus, is a public health concern worldwide. No vaccines or specific antiviral treatment is currently available for chikungunya disease. Thus, it is important to develop inhibitors against CHIKV enzymes to block key steps in viral reproduction. In view of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…The probe, easily prepared by a straightforward solid-phase approach in a highly soluble form, contains the well-known FRET pair Dabcyl-EDANS. 16,17 The donor (EDANS) is separated from the quencher (Dabcyl) by a short peptide linker containing a modified chymotrypsin cleavage site (Pro-Phe) and residues of glutamic acids and lysine at the N-and C-termini, respectively, to potentially increase the cis conformation in solution. Noteworthy, the NMR structural characterization of the probe showed that the cis conformation of the substrate was highly favored, as hypothesized in the design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The probe, easily prepared by a straightforward solid-phase approach in a highly soluble form, contains the well-known FRET pair Dabcyl-EDANS. 16,17 The donor (EDANS) is separated from the quencher (Dabcyl) by a short peptide linker containing a modified chymotrypsin cleavage site (Pro-Phe) and residues of glutamic acids and lysine at the N-and C-termini, respectively, to potentially increase the cis conformation in solution. Noteworthy, the NMR structural characterization of the probe showed that the cis conformation of the substrate was highly favored, as hypothesized in the design.…”
Section: Discussionmentioning
confidence: 99%
“…The intact molecule is thereby internally quenched, while EDANS fluorescence is readily restored upon protease cleavage within the peptide chain and the intensity change can be detected continuously and directly. 16,17 The substrate Ac-EK(Dabcyl)PPFAE(EDANS) KA-NH2 was efficiently synthesized, purified with a high yield (~40%), and characterized by mass spectrometry (Suppl. Table 2).…”
Section: Development Of a Fret Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Region 3 is a serine protease containing a conserved catalytic triad (His 139, Asp 161, and Ser 213) that is able to cleave itself in cis and inactivate itself by binding its active site with its C-terminal tryptophan residue [53,82,83,110]. A recent study reported that the CHIKV capsid is also able to exhibit trans-cleavage properties [111]. In addition, the hydrophobic pocket (containing interacting residues: Val 130, Gly 131, Val 134, Met 135, Trp 245, and Val 250) located on region 3 was found to interact with Pro 404 of the E2 cytoplasmic domain, which is believed to occur during mature particle assembly [102,106,112].…”
Section: Capsid Proteinmentioning
confidence: 99%
“…named capsid, E3, E2, 6K/TF, and E1 proteins, comprised of 261, 64, 423, 61, and 435 amino acids, respectively. The capsid protein (CP) has two domains: the amino terminal domain does not form structural architecture but participates in the formation of nucleocapsid and the interaction with RNA to encapsidate the genome; the carboxyl terminal domain is a serine protease (Weiss et al, 1989;Forsell et al, 1995;Aggarwal et al, 2015); E3 protein is an α/β protein which involves in the regulation of spike assembly and the interaction with its cognate E2 glycoprotein (Snyder and Mukhopadhyay, 2012); E2 glycoprotein is at outermost region of the spike (Smith et al, 1995), having three immunoglobulin domains: A, B and C domains and two glycosylation The CHIKV infection can be completed in 14 steps to generate new viruses. ① Viral E2 glycoprotein binds to the receptors on cell surface.…”
Section: Virologic Characteristicsmentioning
confidence: 99%